Proteomic analysis of jejunum and ileum in rats exposed to acute or chronic fluoride dose - Valle, Aline Dionizio (2020)
The gastrointestinal tract (GIT) is considered the main route of exposure to fluoride (F), which is rapidly absorbed from it. Exposure to this ion can generate considerable changes in the morphology of the intestine, which can affect its functions, leading to gastrointestinal symptoms that represent the first signs of F toxicity. In previous studies performed by our research group, it was observed that exposure to F interferes significantly in the expression of several proteins in the duodenum. Due to the distinct anatomical, histological and physiological characteristics found among the different distinct segments of the small intestine, the present study aimed to evaluate the effect of acute or chronic exposure to F on the proteomic profile of the jejunum and the ileum of rats. Male 60-day-old Wistar rats were treated for 30 days with chronic doses of 0 mgF/L, 10 mgF/L or 50 mgF/L. The acute dose of F (25 mg/Kg body weight) or deionized water (control) was administered once by gastric gavage. After the experimental periods, the jejunum and the ileum were collected. Proteomic analysis of both segments was performed using the nanoACQUITY UPLC-Xevo QTof MS system (Waters, Manchester, UK), in order to better understand the mechanisms involved in acute or chronic F toxicity, which led to the morphological changes observed in our previous studies. The difference in expression between the groups was obtained using the PLGS software, considering p<0.05 and 1-p>0.95 for the for the down and upregulated proteins, respectively. Under acute exposure to F, most of the proteins with altered expression were upregulated in the group 25 mg/Kg F vs. Control. Our results, when analyzed together (jejunum and ileum), suggest that the gastrointestinal symptoms found in these cases may be related to inhibition of protein synthesis by exposure to a high dose of F, such as changes in proteins that regulate the cytoskeleton and energy metabolism, mainly in carbohydrate metabolism. Under chronic exposure to F, most of the proteins with altered expression were upregulated in the group 10 mgF/L vs. control and in the comparison 50 mgF/L vs. control. In the jejunum, there were changes in the abundance of several proteins correlated with protein synthesis, glucose homeostasis, energy metabolism and neural functions. Moreover, in the ileum, a decrease in gastrotropin was found, which may be associated with diarrhea, a common symptom found in cases of F toxicity. In addition, changes in different myosin isoforms were observed, which might have contributed to the structural alterations found in the histological analysis previously performed. In conclusion, acute exposure to F mostly downregulates several proteins, with emphasis on partners involved in protein synthesis, cytoskeleton and energy metabolism, which might help explain the gastrointestinal symptons found in cases of acute exposure to this ion. Distinctly from which was observed for the acute treatment, under chronic treatment with both F concentrations an increase in the expression of proteins was observed, which might indicate an adaptation of the body, in attempt to fight the deleterious effects of this ion.